Gastrointestinal Symptoms in Children With Life-Limiting Conditions Receiving Palliative Home Care - Hauch, Holger; Kriwy, Peter; Hahn, Andreas; Dettmeyer, Reinhard; Zimmer, Klaus-Peter; Neubauer, Bernd; Brill, Sabine; Vaillant, Vera; de Laffolie, Jan; Schaefer, Kristine; Tretiakowa, Irina; Hach, Michaela; et al. (Frontiers in Pediatrics, 2021)
Context: Children with life-limiting diseases suffer from gastrointestinal (GI) symptoms. Since the introduction of specialized palliative home care (SPHC) in Germany, it is possible to care for these children at home. In phase 1 of care the aim is to stabilize the patient. In phase 2, terminal support is provided. Objectives: Analysis were performed of the differences between these phases. The causes and modalities/outcome of treatment were eval-uated. Methods: A retrospective study was performed from 2014 to 2020. All home visits were analyzed with regard to the abovementioned symptoms, their causes, treatment and results. Results: In total, 149 children were included (45.9% female, mean age 8.17±7.67 years), and 126 patients were evaluated. GI symptoms were common in both phases. Vomiting was more common in phase 2 (59.3% vs. 27.1%; p<0.001). After therapy, the proportion of asymptomatic children in phase 1 increased from 40.1% to 75.7%; p<0.001). Constipation was present in 52.3% (phase 1) and 54.1% (phase 2). After treatment, the proportion of asymptomatic patients increased from 47.3% to 75.7% (phase 1); p<0.001), and grade 3 con-stipation was reduced from 33.9 to 15% (phase 2); p<0.05). Conclusion: Painful GI symptoms occur in both palliative care phases but are more common in phase 2. The severity and frequency can usually be controlled at home. The study limitations were the retrospective design and small number of patients, but the study had a repre-sentative population, good data quality and a unique perspective on the reality of outpatient pediatric palliative care in Germany.